Pilot to policy: statewide dissemination and implementation of evidence-based treatment for traumatized youth - Lisa Amaya-Jackson; Dana Hagele; John Sideris; Donna Potter; Ernestine C. Briggs; Leila Keen; Robert A. Murphy; Shannon Dorsey; Vanessa Patchett; George S. Ake; Rebecca Socolar (BMC, 2018)
Abstract Background A model for statewide dissemination of evidence-based treatment (EBT) for traumatized youth was piloted and taken to scale across North Carolina (NC). This article describes the implementation platform developed, piloted, and evaluated by the NC Child Treatment Program to train agency providers in Trauma-Focused Cognitive Behavioral Therapy using the National Center for Child Traumatic Stress Learning Collaborative (LC) Model on Adoption & Implementation of EBTs. This type of LC incorporates adult learning principles to enhance clinical skills development as part of training and many key implementation science strategies while working with agencies and clinicians to implement and sustain the new practice. Methods Clinicians (n = 124) from northeastern NC were enrolled in one of two TF-CBT LCs that lasted 12 months each. During the LC clinicians were expected to take at least two clients through TF-CBT treatment with fidelity and outcomes monitoring by trainers who offered consultation by phone and during trainings. Participating clinicians initiated treatment with 281 clients. The relationship of clinician and client characteristics to treatment fidelity and outcomes was examined using hierarchical linear regression. Results One hundred eleven clinicians completed general training on trauma assessment batteries and TF-CBT. Sixty-five clinicians met all mastery and fidelity requirements to meet roster criteria. One hundred fifty-six (55%) clients had fidelity-monitored assessment and TF-CBT. Child externalizing, internalizing, and post-traumatic stress symptoms, as well as parent distress levels, decreased significantly with treatment fidelity moderating child PTSD outcomes. Since this pilot, 11 additional cohorts of TF-CBT providers have been trained to these roster criteria. Conclusion Scaling up or outcomes-oriented implementation appears best accomplished when training incorporates: 1) practice-based learning, 2) fidelity coaching, 3) clinical assessment and outcomes-oriented treatment, 4) organizational skill-building to address barriers for agencies, and 5) linking clients to trained clinicians via an online provider roster. Demonstrating clinician performance and client outcomes in this pilot and subsequent cohorts led to legislative support for dissemination of a service array of EBTs by the NC Child Treatment Program.